PENGEMBANGAN PENELITIAN TINDAKAN KELAS VIRTUAL LEARNING ECONOMI - Husnaini, Husnaini; Widianti, Santi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstrak— This research was conducted with the aim of assisting teachers in carrying out classroom action research in virtual learning economi. Some of the obstacles experienced by economi teachers in delivering material to students include the educational background of participants who come from outside the department of pure economi or the department of economi education, so they are less able to provide subject matter properly. The method used in this study is the method of implementing this activity by means of Focus Group Discussion (FGD) and continued with the practice of Virtual Learning and CAR. There were 15 economi teacher participants from several schools. The results of this activity in the form of (a) mapping the topic of high school sociology material, (b) increasing the basic knowledge of teachers one of which gives insight into material knowledge, methods and models of economi learning, gives insight into material knowledge of virtual learning skills (learning houses), gives insight into material knowledge classroom action research, (c) the practice of introducing the basic use of virtual learning media